Origins of Relative Age Effects in Youth Football—A Nationwide Analysis - Romann, Michael; Rüeger, Eva; Hintermann, Mirjam; Kern, Raphael; Faude, Oliver (Frontiers in Sports and Active Living, 2020)
Introduction Relative age effects (RAEs) refer to the overrepresentation of players born earlier in the selection year compared to late-born players within the same age category. To date, the origins and mechanisms of RAEs are still unclear. To evaluate the development of RAEs in terms of age group and selection level, we analysed data of all registered child and adolescent football players in Switzerland. Methods Age category, selection level, and birthdate from all licensed 101’991 Swiss child and youth football players assigned to a specific team (9149 girls (9.0%) and 92842 boys (91.0%); age range: 4.6-19.6 years) were analysed. Additionally, out of 1128 clubs, 54 clubs provided their documented waiting lists (1224 players). Birth date distributions were split by age category, sex, and birth quarter (Q1 = January to March, Q4 = October to December). RAEs were calculated using odds ratios (Q1 vs. Q4) with 95% confidence intervals (95%CI). Results We found small RAEs among U8 players (OR 1.44 [95%CI 1.31, 1.59]) and U10 (OR 1.24 [95%CI 1.16, 1.32]). The RAE was negligible in all other age categories, independent of gender. In children’s football 5’584 (71.3%) of teams performed selections. In teams without selection, there were no obvious RAEs. However, in teams with selections for the same age category showed small RAEs with an overrepresentation of Q1 athletes in the first team (OR = 1.29 [95%CI 1.24, 1.35]) and inverse RAEs with an underrepresentation of Q1 athletes in the last team (OR = 0.85 [95%CI 0.82, 0.89]). Only small RAEs were observed on the waiting lists for the U8 (OR = 1.48 [1.13, 1.95]). Discussion and conclusion RAEs have a small, but consistent effect on participation in Swiss children’s football at the grassroots level. Contrary to expectations, no inverse RAEs were found on the waiting lists. Nonetheless, first time coach selections seem to be the origin of RAEs. To protect young athletes from discrimination, RAE-biases should be analysed and eliminated at all stages of sport participation, selection and drop-out situations. Modifications to the organisational structure of sport and athlete development systems are recommended to prevent RAE-related discrimination in youth sports.